Microwave drying characteristics of microalgae (Chlorella vulgaris) for biofuel production - Villagracia, Al Rey C. (Animo Repository, 2016)
Algal biofuels serve as a promising alternative energy source for liquid fuels. However, one of the bottlenecks in the conversion of microalgae to biofuels is the drying process. A moisture content of at most 10 % is desired for algal biomass prior to oil extraction to maximise biofuel yield. Conventional means of drying results to longer drying time and uneven drying of algal biomass. This study investigated the drying characteristics of microwave for microalgae (Chlorella vulgaris). Three microwave intensity levels (300, 600, and 900 W) were considered to dry 10, 20, and 30 of algal mass. Page model gave a better fit on the moisture ratio with time of microwave drying than the exponential model. Furthermore, the specific energy requirement was computed, and a relationship was found between moisture ratio with power and mass. Fourier transform infrared spectroscopy results showed significant reduction of infrared signal intensities of the functional groups present in the algae after drying at higher microwave power level. It was concluded that the 20 W/g microwave drying setting gave a lower specific energy requirement with good quality of remaining high lipid content qualitatively. Furthermore, it was recommended to use gas chromatography mass spectroscopy to further quantify the algal lipids and other functional groups. © 2016, Springer-Verlag Berlin Heidelberg.